Impact of Mindfulness to Relieve Stress, Anxiety, and Depression among the University Students of Odisha - Maharana, Nilamani; Goswami, Rupashree; Behera, Deepak Kumar (PT. Riset Press International, 2023)
Background of the study: Stress, anxiety, and depression are rather common during higher education time and have a bad effect on academic performance. There is evidence that mindfulness practices can enhance the mental health and exist over how stress, anxiety, and depression are affected. In this study, the post-graduate students of Odisha were assessed to see how well mindfulness treated their stress, anxiety, and depression symptoms. Objective: To assess the impact of mindfulness on stress, anxiety, and depression among the post-graduate students of Odisha. Methods: Several articles were searched from different online platforms like PubMed, PsycINFO, Google scholar etc. After searching many articles, the data were collected from online survey among the post-graduate students of Odisha by using two questionnaires; those are “FFMQ-15” and DASS-21. The data collected from the post-graduate students inviting them to take part in the online and offline survey during the academic year 2021-2022. This study was selected only as a sample here for the post-graduate students of Odisha. The present study was conducted on the sample of 220. The data were calculated through statistical package for social sciences (SPSS-20 version). Findings: The result shows that the mindfulness reduced stress, anxiety, and depression of post-graduate students of Odisha. The participants reported considerably bigger gains in mindfulness as well as greater decrease in stress, anxiety, and depression. Implication of the Study: The study's findings will raise awareness among the post-graduate students or people from all lifestyles. The mindfulness practice can reduce all type of physical and psychological stress. Moreover, it reduces the academic anxiety and depression.